The Evolution and Preservation of the Old City of Lhasa - Li, Qing (Springer Singapore, 2018)
This book is the first to provide an in-depth analysis about the history, urban development, planning, and preservation of the Lhasa city over the last thirteen centuries. It studis the old Lhasa city as part of Tibet's social and historical evolution process, therefore, the book presentes a relatively wide angle of vision and objective understanding. The research draws on an unparalleled amount of archival sources as well as up-to-date findings of original research projects. In the meanwhile, some experiences of other Chinese historical cities are also included for comparison with the preservation of the old Lhasa city. This book also contains many unique first-hand photos and high-quality illustrations. They can be used as a reference for scholars and students who are interested in the field of historical and cultural preservation in Chinese urban planning and construction. The book can also be useful to tourists or the people who are interested in the cultural and religious history of Tibet. .